2020
DOI: 10.1002/prp2.584
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐based gene delivery to macrophage mitochondria for atherosclerosis therapy

Abstract: Atherosclerosis with associated cardiovascular diseases remains one of the main causes of disability and death worldwide, requiring development of new solutions for prevention and treatment. Macrophages are the key effectors of a series of events involved in atherogenesis, such as inflammation, plaque formation, and changes in lipid metabolism. Some of these events were shown to be associated with mitochondrial dysfunction and excessive mitochondrial DNA (mtDNA) damage. Moreover, macrophages represent a promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 126 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…As the leading cause of myocardial infarction and stroke (70), atherosclerosis (AS) is a complex disease and involves a series of pathophysiological processes such as inflammation and lipid metabolism (71). Hubacek et al demonstrated that the frequency of LBP 1306T>C (rs2232618) C allele (Leu436) homozygotes is about threefold in patients with myocardial infarction than in controls (60).…”
Section: Lbp-snps In Metabolic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…As the leading cause of myocardial infarction and stroke (70), atherosclerosis (AS) is a complex disease and involves a series of pathophysiological processes such as inflammation and lipid metabolism (71). Hubacek et al demonstrated that the frequency of LBP 1306T>C (rs2232618) C allele (Leu436) homozygotes is about threefold in patients with myocardial infarction than in controls (60).…”
Section: Lbp-snps In Metabolic Disordersmentioning
confidence: 99%
“…As the leading cause of myocardial infarction and stroke ( 70 ), atherosclerosis (AS) is a complex disease and involves a series of pathophysiological processes such as inflammation and lipid metabolism ( 71 ). Hubacek et al.…”
Section: Correlation Between Snp In Lbp Gene and Infections Inflammatory Diseases Metabolic Disorders And Cancersmentioning
confidence: 99%
“…With the development of genetics and molecular biology, growing evidence suggests that the pathogenesis of AS involves lipid metabolism, inflammation, oxidative stress, and innate and adaptive immune responses, which provide new perspectives for the treatment of atherosclerotic plaques. [118] Based on the microenvironment of vulnerable atherosclerotic plaques, the emergence of nanomedicine has brought numerous novel therapeutic strategies, achieving precise therapy for atherosclerotic plaques and boosting the efficacy of current plaque treatments (see Table 2)…”
Section: The Targeting Strategies For the Therapy Of Vulnerable Ather...mentioning
confidence: 99%
“…It is therefore possible that mtDNA damage is the primary event that induces excessive ROS generation, violation of the mitochondrial membrane potential and mitochondrial dysfunction followed by the release of cytochrome C and activation of apoptotic pathways. In addition, damaged mtDNA can be recognized by the body as an endogenous damage-associated molecular pattern (DAMP), which provokes the inflammatory response ( 26 ).…”
Section: The Role Of Mitochondria In the Pathogenesis Of Atherosclerosismentioning
confidence: 99%
“…Penetration through the outer and inner membranes of the mitochondria by these particles is ensured by the presence of hydrophobic and positively charged ligands that facilitate the process of endosomal transport. Lipid carriers are currently regarded as low toxic and highly selective transport systems ( 26 ).…”
Section: Mitochondrial Therapiesmentioning
confidence: 99%